2014
DOI: 10.1016/j.memsci.2013.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of gas permeability of block-segregated polymeric membranes by an effective medium model

Abstract: A complete series of aliphatic aromatic copoly(ether-imide)s, based on aromatic dianhydrides (BPDA, BKDA or PMDA) and mixtures of an aromatic diamine (ODA) and an aliphatic diamine terminated poly(ethylene oxide) PEO(2000) (Mw=2000 g/mol) or PEO(6000) (Mw= 6000 g/mol), has been synthesized using different PEO contents. Cast films of these copolymers have been thermally treated to ensure the segregation of the linear PEO chains from the aromatic portion of these copoly(ether-imide)s. Gas permeability (O 2 , N 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 48 publications
7
15
0
Order By: Relevance
“…The TGA data shows a significant mass loss at 400 °C in all of the PEG‐containing compounds, which is most likely due to the degradation of the PEG component of the PEG‐containing polyimides, with the mass loss increasing as the amount of PEG incorporated in the polymer increases. The significant mass loss around 400 °C that is attributed to PEG degradation occurs at a temperature similar to mass losses around 250 to 450 °C that were attributed to the PEG component in similar PEG‐containing copolymers in previous work . The significant mass loss at 550 °C occurs across all of the materials and is likely due to the degradation of the polyimide component.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The TGA data shows a significant mass loss at 400 °C in all of the PEG‐containing compounds, which is most likely due to the degradation of the PEG component of the PEG‐containing polyimides, with the mass loss increasing as the amount of PEG incorporated in the polymer increases. The significant mass loss around 400 °C that is attributed to PEG degradation occurs at a temperature similar to mass losses around 250 to 450 °C that were attributed to the PEG component in similar PEG‐containing copolymers in previous work . The significant mass loss at 550 °C occurs across all of the materials and is likely due to the degradation of the polyimide component.…”
Section: Resultssupporting
confidence: 71%
“…The R groups in polyimides can also contain nonaromatic polymer components, such as PEG. Previous studies have been done on PEG‐containing polyimides similar to those in the current work and provide insight into the structure and important parameters in these polymer systems, but more information on the interpretation of the SAXS results is needed to fully understand these types of materials . Properties such as gas permeability and selectivity were also shown to depend on the polyimide bridging groups due to variations in free volume and the ability of the polymer chains to participate in close packing …”
Section: Introductionmentioning
confidence: 62%
“…Specifically, there is <5% mass loss of the compounds for temperatures up to around 200°C, which is a more‐than‐adequate expected operating window for the fuel cell. The significant mass loss around 400°C is attributed to PEG degradation and occurs at a temperature similar to mass losses assigned to the PEG component in previously studied PEG‐containing polyimides at around 250–450°C . The significant mass loss occurring around 550°C was attributed to the polyimide phase degradation and also occurs around the same temperature as mass losses that were assigned to the aromatic polyimide component in previously studied PEG‐containing polyimides at around 450°C and higher .…”
Section: Resultssupporting
confidence: 68%
“…Polyimides, both with and without PEG, have been studied previously and have been found to exhibit differences in structural order, interactions, and free volume, which can impact behavior and properties. These material variations can be achieved through the specific choice of aromatic monomers . In this work, protic liquids, including ionic liquids, have been incorporated into some of the polymer membranes in order to provide the ion conduction capability, both the membrane ion source and vehicle, so polymer–ionic liquid interactions are expected to influence performance.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the permeability, several parameters have been studied, and it was found that the main parameters were the content and the chain length of the PEO segments in the polymer . In general, higher content generates a continuous PEO phase which favors the permeability, and higher chain length promotes richer polyether areas, which favors the diffusion of the gas through the polymer …”
Section: Introductionmentioning
confidence: 99%